Remote work in Peru during the COVID-19 pandemic - Alexander Frank Pasquel Cajas; Verónica Tomasa Cajas Bravo; Roberto Carlos Dávila Morán (Administrative Sciences, 2023)
The objective of this research is to investigate the characteristics of remote work in Peru during the COVID-19 pandemic. In addition, the study will allow exploring the advantages, disadvantages, challenges and opportunities that Peruvian remote workers face during this crisis scenario. This was a basic-type, descriptive-level study employing a quantitative approach and a non-experimental design. The sample consisted of 275 workers from two companies located in Metropolitan Lima, and the data were collected in the year 2021. A questionnaire with 30 questions was proposed for data collection; it was validated by three experts, and its reliability was » = 0.85. The findings of the remote work variable place it at a medium level with 40.73%; in the flexibility dimension, the medium level prevailed with 42.55%; the autonomy dimension exhibited a high level with 41.09%; and the productivity dimension exhibited a medium level with 43.64%. In the technology dimension, the low level prevailed with 36.36%, while the psychosocial risks dimension exhibited a medium level with 33.18%. In conclusion, the characterization of remote work in Peru during the COVID-19 pandemic allowed us to establish the most relevant aspects that affected workers who migrated to this form of work.
Keywords: 350; autonomy; flexibility; productivity; psychosocial risks; remote work; technology